2009
DOI: 10.1136/jmg.2008.065953
|View full text |Cite
|
Sign up to set email alerts
|

Penetrance of marked cognitive impairment in older male carriers of the FMR1 gene premutation

Abstract: Male carriers of midsize to large premutation alleles had a sixfold increased risk of developing cognitive decline and the risk increases with allele size. In addition, it was observed that cognitive impairment may precede motor symptoms. These data provide guidance for genetic counselling although larger samples are required to refine these estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 44 publications
2
49
0
4
Order By: Relevance
“…Although some studies showed evidence of earlier age of onset of FXPOI and higher penetrance of mid-range premutations of 80 -100 repeats, 24,25 we chose to use the definition of higher risk alleles of Ն70 repeats in our calculation as defined by Rohr et al 22 We choose to use Ն70 repeats in our calculations for FXTAS and FXPOI for consistency in defining larger premutation alleles and because several studies examined penetrance of larger premutation alleles in FXTAS and FXPOI. 16,17,22 …”
Section: Discussionmentioning
confidence: 99%
“…Although some studies showed evidence of earlier age of onset of FXPOI and higher penetrance of mid-range premutations of 80 -100 repeats, 24,25 we chose to use the definition of higher risk alleles of Ն70 repeats in our calculation as defined by Rohr et al 22 We choose to use Ն70 repeats in our calculations for FXTAS and FXPOI for consistency in defining larger premutation alleles and because several studies examined penetrance of larger premutation alleles in FXTAS and FXPOI. 16,17,22 …”
Section: Discussionmentioning
confidence: 99%
“…The common features of FXTAS are cognitive decline, autonomic dysfunction, neuropathy, and psychiatric features such as anxiety, depression, and apathy (16,(19)(20)(21). Impairments in executive function abilities including working memory, inhibitory control and visuospatial processing begin as early as middle adulthood, and progressively worsen with increasing age (22)(23)(24)(25)(26).…”
Section: Fxtasmentioning
confidence: 99%
“…; K) Axial 3D FLAIR of patient 2 shows no marked HI in the white matter. (Sevin et al, 2009). Cognitive decline in FXTAS usually occurs in men, after a long duration of extrapyramidal disturbances, but it may also occur in women.…”
Section: Advances In Neuroimaging In Fxtas and Future Needsmentioning
confidence: 99%